Management of a medical entity based on models of competitiveness of enterprises on the example of Corten Medic Medical Center - Agnieszka Sikora; Tomasz Sikora; Magdalena Bogdan (Kazimierz Wielki University, 2022)
Competitiveness of a company is one the most crucial determinates in the managing process which is independent of the sector of the economy. This issue is distinctively complex in the health care sector, for the specificity of the service it provides - saving lives and good health of patients. Therefore, the healthcare sector of the economy, the mechanisms, and processes that it undergoes are specific and different from other free market sector. This specificity also refers to competitiveness aspect in the health care sector. The aim of the research was primary analysis of competitiveness factors and determinants in the health care sector. A proper overview of potential enterprise competitiveness models has also been carried out, which could be implemented in managing of health care unites. With accordance to the presented analysis of the available models, cause and effect model competitiveness model has been chosen to analyse and asses CM Corten Medic health care unit's competitiveness potential.